Two-year efficacy and safety of erenumab in participants with episodic migraine and 2–4 prior preventive treatment failures: results from the LIBERTY study. Issue 3 (29th November 2021) - Ferrari, Michel Dominique; Reuter, Uwe; Goadsby, Peter J; Paiva da Silva Lima, Gabriel; Mondal, Subhayan; Wen, Shihua; Tenenbaum, Nadia; Pandhi, Shaloo; Lanteri-Minet, Michel; Stites, Tracy
Abstract : Objective: To evaluate individual and group long-term efficacy and safety of erenumab in individuals with episodic migraine (EM) for whom 2–4 prior preventatives had failed. Methods: Participants completing the 12-week double-blind treatment phase (DBTP) of the LIBERTY study could continue into an open-label extension phase (OLEP) receiving erenumab 140 mg monthly for up to 3 years. Main outcomes assessed at week 112 were: ≥50%, ≥75% and 100% reduction in monthly migraine days (MMD) as group responder rate and individual responder rates, MMD change from baseline, safety and tolerability. Results: Overall 240/246 (97.6%) entered the OLEP (118 continuing erenumab, 122 switching from placebo). In total 181/240 (75.4%) reached 112 weeks, 24.6% discontinued, mainly due to lack of efficacy (44.0%), participant decision (37.0%) and adverse events (AEs; 12.0%). The ≥50% responder rate was 57.2% (99/173) at 112 weeks. Of ≥50% responders at the end of the DBTP, 36/52 (69.2%) remained responders at ≥50% and 22/52 (42.3%) at >80% of visits. Of the non-responders at the end of the DBTP, 60/185 (32.4%) converted to ≥50% responders in at least half the visits and 24/185 (13.0%) converted to ≥50% responders in >80% of visits. Change from baseline at 112 weeks in mean (SD) MMD was −4.2 (5.0) days. Common AEs (≥10%) were nasopharyngitis, influenza and back pain. Conclusions: Efficacy was sustained over 112 weeks in individuals with difficult-to-treat EM for whom 2–4 prior migraine preventives had failed. Erenumab treatment was safe and well tolerated, in-line with previous studies. Trial registration number: NCT03096834